pH Variation during Bioaccumulation of Selected Toxic Metals by Newly Isolated Microscopic Fungi from the Ostramo Lagoons - Marketa Vašinková (Engineering Proceedings, 2023)
The emergence of new biotechnologies has increased interest in the study of the impact of environmental contamination on microbial communities, particularly in relation to the potential benefits that stress-adapted microorganisms offer in environmental protection, industrial ecology, and mineral and waste processing. This study aimed to compare the bioaccumulation abilities of recently isolated microscopic fungi belonging to the genera Aspergillus, Phoma, Cystobasidium, Cladosporium and Exophiala. These fungi were isolated from a site contaminated with both toxic metals and organic pollutants. The study monitored the bioaccumulation of selected toxic metal ions (Cu(II), Zn(II), Ni(II), Cr(III), Pb(II)), as well as pH changes, over a 30-day of biomass growth. The medium containing Pb(II) exhibited a statistically significant pH change during the 30-day accumulation period (Mann-Whitney U Test, p < 0.05). These findings provide valuable insights for the potential industrial application of microscopic fungi in bioaccumulation processes.